Pengaruh Online Consumer Review dan Product Knowledge Terhadap Keputusan Pembelian Laptop Second di Bukalapak - Febrianawati; Nur Hidayat (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2023)
The aim of this study is to analyze the influence of online consumer reviews and product knowledge on the decision to buy a second laptop in Bukalapak. The object of the research used is a consumer who has purchased a second laptop in Bukalapak. The independent variables in this study are Online Consumer Review and Product Knowledge while the dependent variable is Purchase Decision. The data analysis used is simple regression analysis. The results of this study showed that the Online Cunsomer Review (X1) coefficient value against Purchase Decision (Y1) of 0.531, which means that the better Online Cansomer Review read or obtained by the consumer will drive improved purchase decision of second laptop in Bukalapak.